Wandering Spleen: A Narrative Review of Clinical Spectrum, Pathogenesis, Emerging Diagnostics, and Management Approaches - Kyatham Shishir; Chandrashekhar Mahakalkar; Suresh Chandak; Mohammed Azeem Khan; Bhagyesh Sapkale (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Wandering Spleen (WS) is an uncommon clinical disorder in which the spleen is abnormally mobile as a result of either congenital ligamentous anomalies or acquired laxity and thus put at risk of torsion, infarction and variable abdominal symptoms. WS has a bimodal distribution in the age group, which includes children and women of reproductive age and is characterised by non specific symptoms, such as a mobile mass in the abdomen or pelvis, intermittent pain, in few severe cases, an acute abdomen. Diagnosis is not easily done and is dependent much on imaging methods like ultrasound with Doppler, Contrast-Enhanced Computed Tomography (CECT), nuclear scintigraphy, dynamic Magnetic Resonance Imaging (MRI) and newer modalities like Contrast-Enhanced Ultrasound (CEUS). Spleen preservation through splenopexy which is laparoscopic, open, or robotically done is prioritised in the management and splenectomy is used in case of non viable spleen or infarction or sepsis complications. It is important to prevent severe complications by recognising them early and applying proper intervention. The present review will outline the pathogenesis, clinical manifestation, emerging diagnostic methods and the modern management of WS including the most minimal invasive and spleen-sparing techniques.